Potentiometric sensor for sorbic acid determination in food products - Santini, Alberto O. [UNESP]; Pezza, Helena Redigolo [UNESP]; Carloni-Filho, Joao [UNESP]; Sequinel, Rodrigo [UNESP]; Pezza, Leonardo [UNESP] (Elsevier B.V., 2009)
The construction, evaluation and application of a new potentiometric sensor, namely, Pt vertical bar Hg vertical bar Hg(2)(SOB)(2) vertical bar Graphite, where SOB stands for sorbate ion, are described. This electrode has a wide linear dynamic range between 5.0 x 10(-7) and 1.0 x 10(-2) mol L(-1) with a near-Nernstian slope of (-58.6 +/- 1.3) mV decade(-1) and a detection limit of 4.3 x 10(-7) mol L(-1). The potentiometric response is independent of the pH of the solution in the pH range 6.0-9.0. The electrode is easily constructed at a relatively low-cost with fast response time (within 15-30 s) and can be used for a period of 4 months without significant change in its performance characteristics. The proposed sensor displayed good selectivities over a variety of other anions (carboxylates and inorganic anions). The potentiometric sensor was successfully applied to the determination of sorbic acid in real food samples, that is, soft drinks, skim yogurts, jams and sauces. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Sorbate-sensitive electrode; Potentiometry; Soft drinks; Skim yogurts; Jams; Sauces